2016
DOI: 10.1038/srep33446
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Genetic Ancestry and Legacy of 10th Century AD Hungarians

Abstract: The ancient Hungarians originated from the Ural region in today’s central Russia and migrated across the Eastern European steppe, according to historical sources. The Hungarians conquered the Carpathian Basin 895–907 AD, and admixed with the indigenous communities. Here we present mitochondrial DNA results from three datasets: one from the Avar period (7th–9th centuries) of the Carpathian Basin (n = 31); one from the Hungarian conquest-period (n = 76); and a completion of the published 10th–12th century Hungar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 33 publications
4
36
1
6
Order By: Relevance
“…All stages of the work were performed under sterile conditions in a dedicated ancient DNA laboratory (Laboratory of Archaeogenetics in the Institute of Archaeology, Research Centre for the Humanities, Hungarian Academy of Sciences) following well-established ancient DNA workflow protocols 20,54 . The laboratory work was carried out wearing clean overalls, facemasks and face-shields, gloves and over-shoes.…”
Section: Ancient Dna Workmentioning
confidence: 99%
“…All stages of the work were performed under sterile conditions in a dedicated ancient DNA laboratory (Laboratory of Archaeogenetics in the Institute of Archaeology, Research Centre for the Humanities, Hungarian Academy of Sciences) following well-established ancient DNA workflow protocols 20,54 . The laboratory work was carried out wearing clean overalls, facemasks and face-shields, gloves and over-shoes.…”
Section: Ancient Dna Workmentioning
confidence: 99%
“…khagan) and institutions recognized to be derived from Inner Asian Rourans. From the Avar period only a few mitochondrial DNA (mtDNA) data are available from two micro-regions, 3,4 which showed 15.3% and 6.52% frequency of East Eurasian elements. A recent manuscript described 23 mitogenomes from the 7 th -8 th century Avar elite group 5 and found that 64% of the lineages belong to East Asian haplogroups (C, D, F, M, R, Y and Z) with affinities to ancient and modern Inner Asian populations corroborating their Rouran origin.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of forensic genetics, the mtDNA is also a so-called historical marker analyzed by Sanger sequencing technologies [179]. This method combined with capillary array instrumentation or the application of pyrosequencing technology was previously ubiquitous in laboratories [180,181] and is currently still in use [182][183][184].…”
Section: Brief History Of Uniparental Lineage Markersmentioning
confidence: 99%